Effect of dietary choline and diet fermentability on feeding behavior and performance of postpartum dairy cows - Pasch, Kelsey Rose (My University, 2026)
Depressed intake and hepatic lipid accumulation are major contributors to metabolic stress in transition dairy cows. Highly fermentable diets have also been shown to depress dry matter intake (DMI), compounding the risk of metabolic stress. Choline is commonly supplemented to periparturient dairy cows to facilitate hepatic lipid metabolism and support postpartum health and performance. Our objective was to evaluate effects of diet fermentability (DF) and rumen-protected choline (RPC) on postpartum DMI and performance. Multiparous Holstein cows (n = 65) were enrolled on a rolling basis according to body condition score, expected calving date (ECD), and 305-d mature equivalent milk yield, and were randomly assigned to 1 of 4 postpartum treatments in a randomized complete block design with a 2x2 factorial arrangement of starch fermentability rate (low [dry-rolled corn; LFERM] vs. high [wheat; HFERM]) and RPC (no RPC [C-] vs. RPC [C+; 30 g/d]). Prepartum RPC supplementation began 21 d before ECD in a total mixed ration for C+ cows and continued postpartum, whereas C- cows received no RPC. Cows were fed with a Roughage Intake Control (RIC) computerized feeding system during the prepartum period (Hokofarm Group, Emmeloord, The Netherlands). Postpartum cows (n = 55) were fed for 21 d postpartum in a tie-stall with a computerized feeding behavior system. Feeding behaviors, DMI, and milk yield were collected daily, and milk components were collected 2 d/wk. Data were analyzed using linear mixed models for the fixed effects of treatment, time, and their interactions using PROC MIXED in SAS (v 9.4). Means are presented with 95% confidence interval. Prepartum, C+ decreased DMI compared with C- (14.8 [13.8, 15.9] vs. 17.1 kg [16.0, 18.2]). Postpartum, there was no evidence of treatment effect on DMI. Time and RPC interacted for meal size, with C- increasing meal size more rapidly than C+ through d 10 and after d 15. Time and DF interacted to influence milk yield with HFERM increasing milk yield after d 3 compared with LFERM. Compared with LFERM, HFERM decreased milk fat % (4.4 [4.0, 4.8] vs 4.8% [4.4, 5.2]) but not fat yield. Time and DF interacted on protein % and yield; HFERM decreased protein yield from wk 1 to 3 (3.1 [2.8, 3.4] vs. 2.8 [2.6, 3.1]), but there was no difference across wk for LFERM. Compared to LFERM, HFERM decreased milk fatty acid concentrations and preformed fatty acids. There was no evidence of treatment effects on ECM or FCM. For blood metabolites, C+ decreased plasma BHB (1.0 mmol/L [0.9, 1.2] vs. 1.3 [1.1, 1.5]) and tended to increase glucose concentration (49.0 mg/dL [46.4, 51.5] vs. 46.0 [43.5, 48.5]) compared to C-. Time and DF interacted on BUN with HFERM increasing BUN concentration (13.5 mg/dL [12.4, 14.5] vs. 12.6 [11.5, 13.6]). In conclusion, supplementation of RPC, even at a low rate of inclusion, decreased plasma BHB concentrations suggesting improved metabolic status postpartum. Prepartum DMI was reduced in cows supplemented with RPC, which requires further work to elucidate potential mechanisms of action showing similar results in TMR-fed cows. Diet fermentability and RPC supplementation did not interact to affect feeding behavior, which may be reflective of relatively lesser differences in starch digestibility between treatments than anticipated. Formulated starch digestibility was 60.1% for HFERM and 44.6% for LFERM, whereas actual analyzed values were 53.8% and 46.7%, respectively, suggesting that modest differences in starch fermentability may have limited treatment responses.
Keywords: Diet fermentability; Rumen-protected choline; Feeding behavior; Dairy cattle; Transition period